Analysis of Decision Making in Business Strategy of PT GotoGojek Tokopedia - Yulion, Dike Abrila Putri; Alifya, Ananta Rahma; Damayanti, Fitria Ayu Kartika; Hidayat N, Rusdi; Kusumasari, Indah Respati (Indonesian Journal Publisher, 2025)
Decision making is one of the key aspects of business strategy that can determine the success or failure of a company. The purpose of this study is to analyze the impact of strategic decisions on the business sustainability of PT GoTo Gojek Tokopedia, one of the largest technology companies in Indonesia. The focus of this research is to assess the effectiveness of decision making on operational, financial and human resource management aspects and their impact on the company's competitiveness in the market. Using a qualitative approach and secondary data analysis, the findings reveal that PT GoTo's strategic decisions have a significant impact on operational efficiency and adaptability to market trends. However, there are challenges to overcome, such as consistent strategy execution and risk management. This study provides important insights for business professionals to effectively make strategic decisions to gain a competitive advantage.